Asas dan Norma Hukum Administrasi Negara dalam Pembuatan Peraturan Daerah - Rayani Saragih; Maria Ferba Editya S (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
Abstract is written briefly and factually, covering research objectives, research methods, results and This study aims to analyze and find out about laws and regulations, policies and decisions according to state administrative law as well as the principles and norms of state administrative law in making Regional Regulations (Perda). This research method is a juridical normative research using qualitative analysis. Data collection techniques are carried out by library research related to research problems using relevant literature and laws and regulations. This study concludes that the conclusion in this study is that the legal basis for the formation of regional regulations is the 1945 Constitution of the Republic of Indonesia, Law Number 10 of 2004 concerning the Establishment of Legislation, Law Number. 32 of 2004 concerning Regional Government. The formation of regional regulations is carried out based on the hierarchy of laws and regulations and fulfills formal and formal requirements. Regional regulations must also contain norms and principles in the formation of regional regulations, including the principles of the formation of legislation, the principle of legal material concerning the substance of the legislation